Banks, consumers and regulation - Cartwright, Peter, 1968- (Hart Pub., 2004)
Recent developments in law, public policy, and regulation have ensured that questions regarding the relationship between banks and their customers have seldom been out of the spotlight. This important book provides a timely, original, and critical examination of the role of the law in regulating banks in the interests of the consumer.